Occupational exposure to styrene in the fibreglass reinforced plastic industry: comparison between two different manufacturing processes / Esposizione professionale a stirene in industrie di vetroresina: confronto tra due diversi processi produttivi - Tranfo, Giovanna; Gherardi, Monica; Paci, Enrico; Gatto, Mariapia; Gordiani, Andrea; Caporossi, Lidia; Capanna, Silvia; Sisto, Renata; Papaleo, Bruno; Fiumalbi, Carla; Garofani, Patrizia (La Medicina del Lavoro, 2012)
Summary Background: Styrene is used in manufacturing fiberglass reinforced plastics: and occupational exposure was related to neurotoxicology and genotoxicity. The sum of the metabolites mandelic and phenylglyoxylic acids is the ACGIH biomarker for occupational exposure with a BEI of 400 mg/g of creatinine in end shift urine corresponding to an airborne styrene concentration of 85 mg/m3. There are two main molding processes, open and closed, the last more effective at controlling worker’s styrene exposure. Objectives: To compare the open molding process to the compression of fiber reinforced resin foils , a kind of closed molding, monitoring the styrene exposure of workers in two production sites (A and B). Methods: Environmental Monitoring was carried out by Radiello® samplers and Biological Monitoring by means of the determination of MA and PGA with HPLC/MS/MS in 10 workers at Site A and 14 at Site B. Results: The median values for styrene exposure resulted 31.1 mg/m3 for Site A and 24.4 mg/m3 for Site B, while the medians for the sum of the two metabolites in the end shift urine were 86.7 e 33.8 mg/g creatinine respectively. There is a significant linear correlation between personal styrene exposure and the excretion of styrene metabolites(R=0.74). Conclusions: As expected the exposure markers of the workers of the two production sites resulted higher in the open process. The analytical results of both environmental and biological monitoring were all below the occupational exposure limits, confirming the efficacy of the protective devices. Riassunto «Esposizione professionale a stirene in industrie di vetroresina: confronto tra due diversi processi produttivi». Introduzione: Lo stirene è utilizzato nella manifattura plastici rinforzati con fibre di vetro e l’esposizione lavorativa è stata associata con neurotossicità e genotossicità. La somma delle concentrazioni di acido mandelico e fenilgliossilico è l’indicatore biologico ACGIH per l’esposizione lavorativa a stirene, con un BEI di 400 mg/g di creatinina nell’urina di fine turno corrispondente ad 85 mg/m3 di stirene aereodisperso. Esistono due tipi di stampaggio, uno “aperto” e l’altro “chiuso”, più efficace nel ridurre l’esposizione dei lavoratori. Obiettivi: Confrontare il processo aperto con quello di compressione di fogli di resina pronti, assimilabile al processo chiuso, monitorando l’esposizione a stirene dei lavoratori in due aziende (A e B). Metodi: Il monitoraggio ambientale è stato condotto con campionatori Radiello® e quello biologico mediante determinazione di acido mandelico e fenilgliossilico con HPLC/MS/MS su 10 lavoratori dell’azienda A e 14 dell’azienda B. Risultati: I valori mediani per l’esposizione a stirene sono risultati 31,1 mg/m3 per il sito A e 24,4 mg/m3 per il sito B, mentre le mediane della somma dei metaboliti nell’urina di fine turno sono risultate rispettivamente 86,7 e 33,8 mg/g creatinina. La correlazione fra i livelli di esposizione personale a stirene e l’escrezione dei metaboliti urinari è risultata statisticamente significativa (R=0,74). Conclusioni: Come atteso, gli indicatori di esposizione dei lavoratori delle due aziende sono risultati maggiori nel processo aperto. I risultati del monitoraggio ambientale e biologico sono tutti inferiori ai valori limite, confermando l’efficacia dei dispositivi di protezione.